Effect of PCSK9 inhibition in combination with statin therapy on intracranial atherosclerotic stenosis: A high-resolution MRI study - Wu, Lingshan; Kong, Qianqian; Huang, Hao; Xu, Shabei; Qu, Wensheng; Zhang, Ping; Yu, Zhiyuan; Luo, Xiang (Frontiers in Aging Neuroscience, 2023)
Introduction: Intracranial atherosclerotic stenosis (ICAS) is a common cause of stroke worldwide. Evolocumab, a proprotein convertase subtilisin/kexin type-9 inhibitor (PCSK9i), effectively lowers low-density lipoprotein (LDL) and produces favorable changes in coronary atherosclerosis. This study aimed to determine the effects of PCSK9i on intracranial plaques in moderate-intensity statin-treated individuals with ICAS. Methods: This prospective, observational study monitored the imaging and clinical outcomes of individuals with ICAS who were consecutively treated with moderate-intensity statins with or without PCSK9i. Individuals underwent monthly visits and repeat high-resolution magnetic resonance imaging (HR-MRI) at week 12. The primary outcome was a change in HR-MRI after 12 weeks of treatment and the secondary outcome was major vascular events during follow-up. Results: Forty-nine individuals were studied (PCSK9i group: 26 individuals with 28 abnormal vascular regions; statin group: 23 with 27 regions). The PCSK9i group showed a significant reduction in the normalized wall index (0.83 vs. 0.86, p=0.028) and stenosis degree (65.5% vs. 74.2%, p=0.01). Similarly, a greater percentage of individuals with a good response to the efficacy of treatment were treated in the PCSK9i group than that in the statin group (75% vs. 44.4%, p=0.021). The incidence of major vascular events was overall similar between the groups. The treatment options (OR=8.441, p=0.01) and prior diabetes (OR=0.061, p=0.001) were significantly associated with the efficacy of treatment. Discussion: Statin and PCSK9i combination treatment stabilized intracranial atherosclerotic plaques more often compared to statins alone, as documented by HR-MRI. Further study is warranted to determine if combination treatment improves clinical outcomes in ICAS.